E-Module Design Using Kvisoft Flipbook Application Based on Mathematics Creative Thinking Ability for Junior High Schools - Setiyani; Waluya, Stevanus Budi; Sukestiyarno, Y.L; Cahyono, Adi Nur (International journal of interactive mobile technologies, 2022)
Mathematics learning innovations in teaching materials used in schools are still in the form of printed books from the government. In 4.0 era, the use of technology can be used to make teaching materials in the form of e-modules or electronic modules using the Kvisoft Flipbook application. The purpose of this study was to determine the validity, practicality, and student responses to the design of the number pattern e-module based on mathematical creative thinking skills using the kvisoft flipbook application so that it can be used as a learning resource for students both in the classroom learning process and independent learning. The method used in this study is a research and development (R&D) method using the ADDIE model. The data collection technique used is through a validation questionnaire, user practicality questionnaire and student response questionnaire to e-modules. The results of the study show that this e-module is very feasible to use with the results of material expert validation, media expert validation, user practicality, and student responses to e-modules. Based on the results of this study, the design of the e-module using the kvisoft flipbook maker application based on mathematical creative thinking skills is appropriate for use in the learning process for class VIII number pattern material